Glial inflammation as a key regulator and therapeutic target for prion disease - Hay, Arielle, author; Zabel, Mark, advisor; Moreno, Julie, advisor; Tjalkens, Ronald, committee member; Chanda, Soham, committee member; Santangelo, Kelly, committee member (Colorado State University. Libraries, 2023)
Prion diseases are lethal neurodegenerative diseases characterized by the misfolding of the cellular prion protein, PrPC, into the infectious PrPSc. PrPSc accumulation in the brain contributes to the activation of microglia and the subsequent increase in reactive astrocytes, which together contribute to neuroinflammation. PrPSc aggregation triggers and leads to the dysregulation of a variety of cellular stress pathways, including the oxidative stress response, unfolded protein response, ubiquitin-proteosome system, autophagy and lysosomal degradation. Most critically, PrPSc contributes to neuronal toxicity and death, but the mechanism behind this is poorly understood. Prion diseases affect humans and a variety of mammalian species, with no available treatments. The majority of therapeutics developed to combat these diseases have targeted the prion protein itself. As these have been unsuccessful, it is time to turn our attention to treatments that target the cellular pathways and neuroinflammation caused by PrPSc accumulation in the brain. The overarching goal of this work is to identify glial-induced inflammation as a candidate for therapeutic intervention of prion diseases. We assessed the use of mesenchymal stromal cells (MSCs), which are potent regulators of inflammatory signaling and glial polarization, in cell culture and animal models of prion disease. Additionally, we investigate the role of a key inflammatory signaling pathway, Nuclear Factor-Kappa B (NF-κB) in microglial response to prion infection. Our findings both characterize contributions of specific glial cells to prion-induced inflammation, as well as uncovering novel targets for the treatment of prion diseases. First, we assessed the therapeutic potential of adipose-derived mesenchymal stromal cells (AdMSCs) in a cell culture model of glial prion infection. MSCs are known for their ability to migrate to sites of inflammation and produce immunomodulators. We evaluated the ability of cultured AdMSCs to respond to molecular factors present in brain homogenates from prion-infected animals. We found that these cells upregulate anti-inflammatory genes in response to both specific inflammatory cytokines and crude prion brain homogenates. Moreover, AdMSCs migrate towards prion brain homogenates in an in vitro model. Co-culturing AdMSCs with prion-treated BV2 cells or infected primary mixed glial cultures resulted in a significant decrease in markers of inflammation and disease-associated microglia and reactive astrocyte markers. These findings were independent of PrPSc, as AdMSCs had no effect on prion accumulation in mixed glial cultures. Collectively, these findings highlight AdMSCs as an intriguing candidate for modulating glial-induced inflammation in prion disease. Next, we evaluated AdMSCs in a mouse model of prion disease. Prior to delivery into prion-infected mice, AdMSCs were stimulated with TNFα, which we show increases their upregulation of anti-inflammatory molecules and growth factors. Stimulated AdMSCs were delivered intranasally to prion-infected mice every two weeks beginning from early in infection (10 weeks post-infection (wpi)) and ending late in infection (20 wpi). A cohort of mice was euthanized at various stages in infection, at 14 wpi, 16 wpi and 18 wpi. We show that AdMSCs are able to migrate throughout the brain when delivered intranasally, with the most cells being found in the hippocampus and thalamus. Although AdMSCs were not successful in improving behavior or increasing survival in prion-infected mice, they did induce changes in prion pathology at early time points in disease. A decrease was seen in inflammatory cytokines and markers of glial activation. No changes were seen in PrPSc accumulation or neuronal loss compared to untreated controls. However, at both 16- and 18 wpi, we identified significant changes in both glial numbers as well as morphology, indicating that AdMSCs attenuate reactivity in microglia and astrocytes. Together, these findings highlight AdMSCs as potent regulators of prion-induced glial inflammation, and warrants further investigation to optimize these cells as a treatment for prion disease. In addition to assessing therapeutics that decrease inflammation and reprogram glial cells to a homeostatic phenotype, we wanted to better characterize specific inflammatory pathways and understand how these were being regulated in glial cells in response to prion infection. NF-κB-related genes have long been identified in the brains of animal models with prion disease, but studies that have investigated its role in prion pathogenesis have focused on neurons and astrocytes. Microglia are critical innate immune regulators in the brain, and interact closely with both neurons and astrocytes to regulate inflammation and cell survival. Therefore, we saw an immediate need to characterize NF-κB signaling in microglia, and its contribution to prion-induced neuroinflammation. IKβ kinase (IKK) is a complex that responds to cell stressors and is critical for NF-κB signaling to occur. We utilized a primary mixed glial model containing wild-type (WT) astrocytes and IKK KO microglia. Upon infecting these mixed glial cultures with prions, we saw a drastic decrease in NF-κB-related genes compared to cultures containing WT astrocytes and WT microglia. Despite this, cultures containing IKK KO microglia still contribute neurotoxic signals that induce neuronal cell death. Moreover, we found that cultures with IKK KO microglia showed significantly more PrPSc accumulation, suggesting that these cells may have impaired autophagy. This work implicates microglial NF-κB-signaling and IKK as a potent inducer of inflammation and regulator of autophagy in prion disease.
Keywords: microglia; neuroinflammation; astrocytes; prion disease; neurodegeneration